Intracranial Stenting After Failed Thrombectomy in Patients With Moderately Severe Stroke: A Multicenter Cohort Study - Meyer, Lukas; Fiehler, Jens; Thomalla, Götz; Krause, Lars Udo; Lowens, Stephan; Rothaupt, Jan; Kim, Byung Moon; Heo, Ji Hoe; Yeo, Leonard; Andersson, Tommy; Kabbasch, Christoph; Dorn, Franziska; et al. (Frontiers in Neurology, 2020)
Background & Purpose: Recently, acute intracranial stenting (ICS) has gained more interest as a potential bailout strategy for large vessel occlusions (LVO) that are refractory to thrombectomy. However, there are currently no reports on ICS in patients with moderately severe stroke discussing the question if implementing a permanent stent is feasible and leads to improved recanalization after failed thrombectomy. Methods: We analyzed a large multicenter database of patients receiving ICS for anterior circulation LVO after failed thrombectomy. Inclusion criteria were defined as: Moderately severe stroke ( National Institute Health Stroke Scale (NIHSS) ≤9 on admission), anterior circulation LVO, acute ICS after failed stent retriever MT. Primary endpoint was the rate of improved successful recanalization after ICS defined as a modified Thrombolysis In cerebral Infarction (mTICI) score ≥2b. Favorable neurological outcome was defined as an early neurological improvement (ENI) of 4 points or reaching 0 with respect to baseline NIHSS. Results: Forty-one patients met the inclusion criteria. A median of 2 retrievals were performed (IQR 1-4) prior decision-making for ICS. ICS led in 90.2% (37/41) of cases to a final mTICI≥2b with significant improvement (p<0.001) after the last retrieval attempt. The median NIHSS decreased (p=0.178) from 7 (IQR 3.5-8) on admission to 2.5 (IQR 0-8.25) at discharge. ENI was observed in 47.4% (18/38). sICH occurred in 4.8% (2/41). Conclusion: ICS after failed thrombectomy appears to effectively improve recanalization rates in patients with moderately severe strokes. Thus, ICS should be considered also for patients with baseline NIHSS ≤9 if thrombectomy fails.